Coincident measurements of PMSE and NLC above ALOMAR (69° N, 16° E) by radar and lidar from 1999-2008 - Kaifler, N.; Baumgarten, G.; Fiedler, J.; Latteck, R.; Lübken, F.-J.; Rapp, M. (Göttingen : Copernicus, 2011)
Polar Mesosphere Summer Echoes (PMSE) and Noctilucent Clouds (NLC) have been routinely measured at the ALOMAR research facility in Northern Norway (69° N, 16° E) by lidar and radar, respectively. 2900 h of lidar measurements by the ALOMAR Rayleigh/Mie/Raman lidar were combined with almost 18 000 h of radar measurements by the ALWIN VHF radar, all taken during the years 1999 to 2008, to study simultaneous and common-volume observations of both phenomena. PMSE and NLC are known from both theory and observations to be positively linked. We quantify the occurrences of PMSE and/or NLC and relations in altitude, especially with respect to the lower layer boundaries. The PMSE occurrence rate is with 75.3% considerably higher than the NLC occurrence rate of 19.5%. For overlapping PMSE and NLC observations, we confirm the coincidence of the lower boundaries and find a standard deviation of 1.26 km, hinting at very fast sublimation rates. However, 10.1% of all NLC measurements occur without accompanying PMSE. Comparison of occurrence rates with solar zenith angle reveals that NLC without PMSE mostly occur around midnight indicating that the ice particles were not detected by the radar due to the reduced electron density. publishedVersion